The effect of behavioral factors of defecation, drinking water sources and housewives' handwashing habits on the incidence of stunting in the working area of the brand health center - Br Perangin-Angin, Susanti; Sembiring, Haesti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Stunting a critical nutritional issue affecting toddlers in low- and middle-income countries like Indonesia, leads to significant economic losses through reduced productivity, increased healthcare costs, and diminished human resource quality. This study explored how factors such as defecation behavior, drinking water sources, and maternal handwashing habits influence stunting in the Brand Health Center area of Karo Regency. Findings revealed that toddlers aged 0-3 years were predominantly affected by stunting, with 100% of the stunting group showing underweight issues. While gender did not significantly impact stunting rates, nutritional status was severely compromised in the stunting group compared to the control. Maternal income was a notable factor, with lower income linked to higher stunting rates, although maternal education and working status did not show significant correlations. Larger family size and poor sanitation practices were more prevalent in the stunting group, as were unqualified drinking water sources. Handwashing with soap was slightly more common in the non-stunted group but did not significantly affect stunting rates. These results underscore the need for a comprehensive approach to improve clean water access, sanitation, and handwashing practices to address and reduce stunting in affected areas.